Functions of Corporate Social Responsibility (CSR) for Community Empowerment - Putri Nur, Maulidina; Aqil, Muhammad; Al Khaeriyah, Norma; Azzahra Fitriani, Putri (PT Literasi Nusantara Publisher, 2023)
This research focuses on the implementation of community empowerment through CSR (Corporate Social Responsibility) programs. Implementing corporate social responsibility programs by companies that can bring about community independence, because in CSR itself there is implementation of empowerment. Therefore, it is necessary to evaluate the implementation of programs related to CSR, so the program can be implemented on an ongoing basis and can empower communities. This research uses a literature study method by utilizing literature in the form of journals, books, and articles that are relevant to the theme and title of the research. The result of this research is that community empowerment is an ideal method in implementing CSR programs.